Quantification of cellular protein and redox imbalance using SILAC-iodoTMT methodology - Vajrychova, Marie; Salovska, Barbora; Pimkova, Kristyna; Fabrik, Ivo; Tambor, Vojtech; Kondelova, Alexandra; Bártek, Jiří; Hodny, Zdenek (Redox biology, 2019)
Under normal conditions, the cellular redox status is maintained in a steady state by reduction and oxidation processes. These redox alterations in the cell are mainly sensed by protein thiol residues of cysteines thus regulating protein function. The imbalance in redox homeostasis may therefore regulate protein turnover either directly by redox modulating of transcription factors or indirectly by the degradation of damaged proteins due to oxidation. A new analytical method capable of simultaneously assessing cellular protein expression and cysteine oxidation would provide a valuable tool for the field of cysteine-targeted biology. Here, we show a workflow based on protein quantification using metabolic labeling and determination of cysteine oxidation using reporter ion quantification. We applied this approach to determine protein and redox changes in cells after 5-min, 60-min and 32-h exposure to H2O2, respectively. Based on the functional analysis of our data, we confirmed a biological relevance of this approach and its applicability for parallel mapping of cellular proteomes and redoxomes under diverse conditions. In addition, we revealed a specific pattern of redox changes in peroxiredoxins in a short time-interval cell exposure to H2O2. Overall, our present study offers an innovative, versatile experimental approach to the multifaceted assessment of cellular proteome and its redox status, with broad implications for biomedical research towards a better understanding of organismal physiology and diverse disease conditions.
Keywords: Oxidative Stress; Oxidation-Reduction; oxidace-redukce; proteom; tandemová hmotnostní spektrometrie; peroxiredoxiny; Peroxiredoxins; Chromatography, Liquid; Proteome; oxidační stres; Cysteine; chromatografie kapalinová; Tandem Mass Spectrometry; peroxid vodíku; Hydrogen Peroxide; Proteomics; proteomika; cystein